Development Of Web-Based English Learning Media Using Content Management System (Word Press) And Elementor Plugin - Farmana, Yuditra; Yasin, Muhammad (International Journal of Educational Research & Social Sciences, 2022)
This research was conducted based on the importance of English learning media that can be accessed by everyone anytime and anywhere, in this case not limited to the students of STIE Enam Enam Kendari butstudents from other tertiary institutions andeven the general public. It is related to the Ministry of Education,Cultures, Researchand Technology’s program about Freedom to Learn (Merdeka Belajar Kampus Merdeka)which creates a flexible and innovative teaching-learning process. Therefore this research aims to design and develop website-based learning media using a content management system (CMS), namely WordPress and the elementor plugin for English courses at STIE Enam Enam Kendari. The stage of research method used is a"modified waterfall model" which consists of several stages described as follows: Requirement and analysis:the stage for collecting basic information by utilizing the interview method and literature study; SystemDesigning: this stage is used to illustrate flowcharts and design web-based learning media and determine users/accessors; Implementation: the stage of installing a new system; Testing: the stage to ensure the system is running as needed; Deployment: the stage where the system that has been tested is implemented to the user; Maintenance: the stage used to meet the needs for system improvement after being distributed to users.Research findings showed that WordPress as a content management system and elementor plugin are effectivetools to develop and design web-based English learningmedia. It meets the criteria of online learning media aswell. The students can accessthe web-based English learning media to find information about the lessons ormaterials from the 1st to the 16th meeting in certain semesters. In addition, the usersin this case the students’ responses towards the web-based English learning media using WordPress and elementor were categorized as satisfied in all aspects (layout & design; speed web pages load; and learning materials) with the averagenumber ofpercentage 87% (excellent).